Is the Surgical Safety Checklist successfully conducted? An observational study of social interactions in the operating rooms of a tertiary hospital. Issue 8 (8th March 2013) - Cullati, Stéphane; Le Du, Sophie; Raë, Anne-Claire; Micallef, Martine; Khabiri, Ebrahim; Ourahmoune, Aimad; Boireaux, Armelle; Licker, Marc; Chopard, Pierre
Abstract : Objectives: To determine whether the items on the Time Out and the Sign Out of the Surgical Safety Checklist are properly checked by operating room (OR) staff and to explore whether the number of checked items is influenced by the severity of the intervention and the use of the checklist as a memory tool during the Time Out and the Sign Out periods. Methods: From March to July 2010, data were collected during elective surgery at the Geneva University Hospitals, Switzerland. The main outcome was to assess whether each item of the Time Out and the Sign Out checklists have been checked, that is, 'confirmed' by at least one member of the team and 'validated' by at least one other member of the team. The secondary outcome was the number of validated items during the Time Out and the Sign Out. Results: Time Outs (N=80) and Sign Outs (N=81) were conducted quasi systematically (99%). Items were mostly confirmed during the Time Out (range 100–72%) but less often during the Sign Out (range 86–19%). Validation of the items was far from optimal: only 13% of Time Outs and 3% of Sign Outs were properly checked (all items validated). During the Time Out, the validation process was significantly improved among the highest risk interventions (29% validation vs 15% among interventions at lower risk). During the Sign Out, a similar effect was observed (19% and 8%, respectively). A small but significant benefit was observed when using a printed checklist as a memory tool during the Sign Out, the proportion of interventions with almost all validated items being higher compared with those without the memory tool (20% and 0%, respectively). Conclusions: Training on the proper completion of the checklist must be provided to OR teams. The severity of the interventions influenced the number of items properly checked.